2006
DOI: 10.1016/j.cnr.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Autism and the development of face processing

Abstract: Autism is a pervasive developmental condition, characterized by impairments in non-verbal communication, social relationships and stereotypical patterns of behavior. A large body of evidence suggests that several aspects of face processing are impaired in autism, including anomalies in gaze processing, memory for facial identity and recognition of facial expressions of emotion. In search of neural markers of anomalous face processing in autism, much interest has focused on a network of brain regions that are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 232 publications
(292 reference statements)
8
98
0
13
Order By: Relevance
“…Alternatively, early abnormalities in gaze behaviour of the high-risk children (e.g. a focus on irrelevant features of the face such as the hairline and ears) might reduce exposure to internal face features (Golarai et al, 2006) while also increasing the total amount of looking. As the images used in the pop-out task were too small to define separate AOIs around the facial features we investigated the face-scanning patterns of the same group of infants using gaze data that was recorded when they observed the still image of a face during a different task administered during the same testing session (for more information about the task see Elsabbagh et al, 2013b).…”
Section: Face Scanning At 7 Monthsmentioning
confidence: 99%
“…Alternatively, early abnormalities in gaze behaviour of the high-risk children (e.g. a focus on irrelevant features of the face such as the hairline and ears) might reduce exposure to internal face features (Golarai et al, 2006) while also increasing the total amount of looking. As the images used in the pop-out task were too small to define separate AOIs around the facial features we investigated the face-scanning patterns of the same group of infants using gaze data that was recorded when they observed the still image of a face during a different task administered during the same testing session (for more information about the task see Elsabbagh et al, 2013b).…”
Section: Face Scanning At 7 Monthsmentioning
confidence: 99%
“…As previous studies have shown, higher signal in the prefrontal and temporal cortices is considered a likely state or trait biomarker for impaired facial processing abilities in individuals with ASD. 36,37 Thus, as the measured signal decreases during training, it would indicate normalization of brain activity. These results suggest that the fNIRS-based neurofeedback might help with the normalization of brain activity in children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with ASD, the face recognition networks usually include aberrant activation in the fusiform face area and significantly increased activation in the PFC, temporal cortex, or primary visual cortex as compared with TD individuals. 36,37 Among these key brain regions, fNIRS can detect only cortical regions underlying the scalp and skull because of the limited penetration depth of the technique. Therefore, we utilized the brain signal measured from the prefrontal and temporal cortices in our study.…”
Section: Functional Near-infrared Spectroscopy Data Acquisitionmentioning
confidence: 99%
“…Therefore, the severity of ASD symptom does not necessarily correlate with subjective psychological stress or risk of psychiatric comorbidity since individuals with mild or atypical autistic traits may have been covertly suffering from mental health problems associated with interpersonal friction or maladaptation to society. Even if an adult patient does not have a medical history with an ASD diagnosis in childhood, repetitive discouraging experiences emotional dysregulation [108,109], executive dysfunction [51,110], and deficits in cognition of facial emotion [111], whereas BPD also comprises emotional dysregulation, executive dysfunction (i.e., impairments in attention, flexibility, learning, and planning), and deficits in cognition of facial emotion [112][113]. Additionally, another study showed that patients with ASD and patients with personality disorders (almost all subjects were patients with cluster B or cluster C personality disorder) did not differ in their ability to read and regulate emotions [114].…”
Section: Asd and Personality Disordersmentioning
confidence: 99%